2018
DOI: 10.22270/ujpr.v3i3.163
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Helicobacter Pylori Among Asymptomatic Populations in Sana'a, Yemen

Abstract: Helicobacter pylori consider the most important cause of chronic gastritis and also the most important etiological factor responsible for the duodenal and gastric ulcer and have an important role in the pathogenesis of gastric cancer. The aim of the present study to know the prevalence of H. pylori among the khat chewing adults in compared to non-khat chewing among asymptomatic populations. A total of 82 healthy subjects were screened to find out the prevalence of Helicobacter pylori using stool antigen card t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…Furthermore, the study of the metabolic syndrome prevalence according to sex showed a significantly higher prevalence in females (52.9%) %) compared to males (30.4%). This result is similar to many studies 17,18 . However, it was in consistent with others where the prevalence is similar between both sexes 19 .…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, the study of the metabolic syndrome prevalence according to sex showed a significantly higher prevalence in females (52.9%) %) compared to males (30.4%). This result is similar to many studies 17,18 . However, it was in consistent with others where the prevalence is similar between both sexes 19 .…”
Section: Discussionsupporting
confidence: 93%
“…In addition, our study shows Khat chewing to be a risk factor for H. pylori infection, which is in agreement with earlier studies reporting the prevalence of H. pylori infection to be higher among Khat chewers, indicating that Khat chewing could be a predisposing factor to gastrointestinal disorders and H. pylori infection. 24,37,[39][40][41] Khat chewers were reported to be four times more likely to have H. pylori infection than non-Khat chewers. 37 The high prevalence of H. pylori with Khat chewing would also be expected to reduce iron absorption, [42][43][44] since H. pylori increases iron uptake and utilization for metabolism 45 and also leads to blood loss due to gastric lesions as a consequence of infection, 46 and elevates the pH of gastric juice due to infection.…”
Section: Discussionmentioning
confidence: 99%